Program Deteksi Dini Skrining Kesehatan Mental Bagi Warga Binaan Di Rumah Tahanan Kelas IIB Kebumen - Arifan Alyusuf , Berlianto Wisnu; Agustin, Ike Mardiati; Waladani, Barkah; Wardani, Anita Yunia; Husna , Aulia Fajriyatul; Erliningtyas , Fathonia; Savia, Hana; Rosida, Izzatur; Puspaningtyas, Mela (Yayasan Inspirasi El Burhani, 2024)
Introduction: Background According to American psychotic association, Mental health is the result of a successful adjustment or lack of psychopathology. It also refers to a state in which one does not experience a breakdown in psychological aspects, emotional, eehavior, and social. According to who's regional asia Pacific in Indonesia, There are 9,162.886 cases or 3.7 %s of the population. According to basic health research 2018, the case of mental or mental illness in Indonesia has improved, especially on the Central Java, where prevalence of mental illness is approximately 4.4 %. In the prison house, An inmate will face various problems and sufferings. Theoretically, The major suffering the inmates suffered was the loss of freedom of movement. However, There's extra suffering from the loss of this freedom, which is: 1). Lost the chance to have sexual relations. 2). Loss of privacy rights. 3). Lost access to getting help and kindness. 4). Lost personal secrecy due to a negative stigma of society.5). Feeling the infantile process, it's the treatment that makes an adult feel like a child. Observe The purpose of this activity is to Detect Mental Health of Inmates in Kebumen Class IIB Prison. Method: This method of activity uses descriptive analysis methods Result and conclusion: According to the mental health screening prognosis that has been carried out to 135 inmates, the result of questionnaire depressive questionnaires 4.44 % is very bad, anxiety category 4.44 % is severe, and the stress category of 2.22 %s is very severe.Generated questionnaire 24,44 % has a GME/Psychotic /PTSD problem.